A questionnaire survey on sleep environment conditioned by different cooling modes in multistorey residential buildings of Singapore. Issue 1 (January 2017) - Yang, Bin; Olofsson, Thomas
A good sleep environment is essential to maintain a person's health and daily working performance. How to create comfortable and healthy sleep environments with less energy use is worth exploring. Findings, based on one questionnaire survey on sleep environments conditioned by different cooling modes have been reported. The study investigated the use of different cooling devices in relation to the effect on sleep. Human responses to thermal environments and air quality created by different cooling modes were also studied. Totally 229 completed questionnaires were statistically analysed. The results show that most of the respondents prefer to use air conditioner 3–6 months in a year with relatively low temperature settings especially for respondents living below fifth floor. It is better to choose relatively high temperature settings to reduce air conditioning intensity especially for elders and outdoor workers, which can not only avoid cold thermal discomfort but also reduce electric energy use. For elders, outdoor workers and persons living in higher floor levels, there was an increase usage of electrical fans or natural ventilation. Thermal comfort can be maintained by raised air movement and the perceived air quality could improve obviously by introducing outdoor air, which would create a good sleep environment to ensure sleep quality.